Oenothera speciosa Nutt. (Onagraceae) en la provincia de Sevilla (España). - Pulgar Sañudo, Íñigo; Ortega Olmo, Patricia; Herrera Rodríguez, José Manuel (Acta Botanica Malacitana, 2018)
Oenothera speciosa Nutt. (Onagraceae) in the province of Seville (Spain). Palabras clave: Planta adventicia, invasora, nueva cita, Sevilla. Key Words: Adventitious plant, invasive plant, new record, Seville.